A comparative study of endoscopic assisted curettage adenoidectomy with conventional adenoidectomy - Kumar, Abhay; Narayan, Prabhu; Narain, Prem; Singh, Jaypal; Porwal, Prateek Kumar; Sharma, Sanjay (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: In ENT adenoidectomy is a commonly performed surgery. It is conventionally done using the curettage method. This present study aims to evaluate endoscopic assisted curettage adenoidectomy as an alternative. Methods: The present study consisted of forty cases requiring adenoidectomy were divided into two groups of twenty each. In Group A adenoidectomy was done by conventional curettage method and in Group B by endoscopic assisted micro-debrider adenoidectomy. The parameters studied between two groups were intra-operative time, intra-operative bleeding and completeness of resection .The study period was from June 2015 to December 2016. Results: The average time taken in Group A (conventional surgery) was 5.30 minutes and in Group B (powered endoscopic surgery) was 12.30 minute. The average blood loss in Group A was 35 ml (range 10–50) as compared to 30 ml in Group B. Nearly 25 % of the patients who underwent endoscopic assisted adenoidectomy had grade II adenoids. About 30% of the patients who underwent conventional adenoidectomy had Grade III adenoids. A total of 10% of the patients developed primary haemorrhage which was more in conventional adenoidectomy (15%) as compared to endoscopic adenoidectomy (5%). Conclusions:Endoscopic assisted microdebrider adenoidectomy was found to be a safe and effective tool for adenoidectomy. Endoscopic adenoidectomy better for completeness of resection, accurate resection under vision. On the other hand, in conventional adenoidectomy operative time and intra-operative bleeding was less.